Relationship with the Regularity of Visits Complications of Hypertension in Patients more than 45 years old - Wahyu Wijayanto; Prijono Satyabakti (Universitas Airlangga, 2014)
ABSTRACT Hypertension being a risk factor for the entrance of various degenerative diseases such as coronary heart disease, stroke and other vascular Penyait. One factor that may increase the risk of hypertension one of them is poor lifestyle such as smoking, excessive consumption of salt in the diet and lack of exercise. This study was conducted to determine the level of knowledge about the relationship with the regularity of visits Complications of Hypertension Hypertension in Patients 45 years of age at the Tembok Dukuh  health center at Surabaya. The study was an observational cross-sectional study design. Sample size were 48 people that hypertensive patients more than 45 years old  who were treated at the Tembok Dukuh  health center. Independent variables, namely knowledge about the complications of hypertension patients and dependent variable is the regularity of visits to theTembok Dukuh health center patients with hypertension  Data analysis using the crosstab tes The results with cross-tabulation (crosstab) can be seen as many as 30 people from 48 respondents have less knowledge and affect the regularity of visits to the Tembok Dukuh health center. The conclusion can be drawn that most hypertensive patients more than 45 years old whose came to Tembok Dukuh  health centers has less knowledge about hypertension complications that result in hypertensive patients regularity of visits decreased Keyword : hypertension, knowledge, regularity of visits